Effect of copper sulphate on the antioxidant parameters in the rainbow trout fry, Oncorhynchus mykiss - Yonar, M. E.; Ispir, U.; Yonar, S. Mise; Kirici, M. (C M B Assoc, 2016)
The aim of this study was to evaluate antioxidant responses of rainbow trout (Oncorhynchus mykiss) exposed to different concentrations of copper sulphate (CuSO4). Fish were exposed to 0 (Group I-control), 5 (Group II), 15 (Group III) and 30 mu g/L (Group IV) concentrations of CuSO4 for 14 days. Liver and gills samples were collected at the end of the experiment, and analysed for their oxidant-antioxidant status, including the malondialdehyde (MDA) level, the catalase (CAT) and glutathione peroxidase (GSH-Px) activities as well as the reduced glutathione (GSH) concentration. Results obtained showed that the levels of MDA increased in tissues of fish. Compared to control, GSH level and GSH-Px and CAT activities were significantly reduced in the fish that were exposed to different concentrations of CuSO4. The result demonstrated that CuSO4 has an oxidative-stress-inducing potential in fish.
Keywords: Copper sulphate; rainbow trout; oxidative stress; antioxidant system